2011
DOI: 10.2147/opth.s23922
|View full text |Cite
|
Sign up to set email alerts
|

Two-position measurement of intraocular pressure by PT100 noncontact tonometry in comparison with Goldmann tonometry

Abstract: BackgroundThe purpose of this study was to evaluate the precision of intraocular pressure measurements obtained by PT100 noncontact tonometry in a handheld and slit lamp-mounted position in comparison with that of Goldmann applanation tonometry in healthy young adults.MethodsSixty eyes from 60 subjects (30 men and 30 women) aged 22 ± 1 (range 20–24) years participated in this study. Triplicate intraocular pressure measurement of a randomly selected eye was obtained by a noncontact tonometer in a handheld and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Previous studies 29,31,48 that compared IOP measurements with the PT-100 and GAT tonometers found no significant differences between the mean IOPs, but only one study 29 had compared measurements with both devices on two separate sessions. The authors found comparable IOP measurements with both instruments.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Previous studies 29,31,48 that compared IOP measurements with the PT-100 and GAT tonometers found no significant differences between the mean IOPs, but only one study 29 had compared measurements with both devices on two separate sessions. The authors found comparable IOP measurements with both instruments.…”
Section: Discussionmentioning
confidence: 95%
“…Similar to our findings, earlier reports have shown agreement between PT-100 and GAT IOP readings within the normal range of IOP. 22,29,30 In another study that evaluated the performance of the PT-100 tonometer in healthy eyes, the instrument had better repeatability than the GAT. As the LoA between the PT-100 and GAT-measured IOP was within the maximum tolerance range of ±3 mmHg, which was suggested for the validity of a tonometer used to appropriately manage diseases that threaten vision, 39 both tonometers can be used interchangeably in disease management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations